PENGARUH LINGKUNGAN KERJA, KEPRIBADIAN, DAN KOMUNIKASI INTERPERSONAL TERHADAP KOMITMEN ORGANISASI DOSEN UNIVERSITAS DARMA PERSADA DI JAKARTA (2012) - Nani Dewi Sunengsih (Jurnal Manajemen., 2014)
The aim of this research is to obtain information related to the effect of work environment, personality, and interpersonal communication on lecturers’ organizational commitment of Darma Persada University in Jakarta. Survey was conducted in this research with 100 sample of lecturers selected randomly. Data have been analyzed by path analysis. The findings of this research show that (1) work environment effects directly on lecturers’ organizational commitment; (2) personality effects directly on lecturers’ organizational commitment; and (3) interpersonal communication effects directly on lecturers’ organizational commitment; (4) work environment effects directly on lecturers’ interpersonal communication; and (5) personality effects directly on lecturers’ interpersonal communication. Based on those findings it can be concluded that any concern toward work environment, personality, and interpersonal communication on lecturers’ organizational commitment of Darma Persada University in Jakarta. Therefore, work environment, personality, and lecturers’ interpersonal communication should be put into strategic planning of human resources development in increasing organizational commitment of Darma Persada University in Jakarta.